An evaluation of public affairs and Parliamentary Support Trust’s (PAPST) Constituency Development Programme (CDP) in Gokwe Central Constituency - Honzeri, Acknella (Midlands State University, 2014)
This research is an evaluation of the impacts of Public Affairs and Parliamentary Support Trust’s (PAPST) Constituency Development Programme (CDP) in Gokwe Constituency. It has attempted to collect, describe and analyze the extent to which the lives of the people in Gokwe Constituency were changed by PAPST initiatives. The major findings of the research were that the CDP initiatives greatly changed the lives of the Gokwe constituents, their socio-economic and political ways of life. These findings are fused with theoretical framework developed earlier from the literature that was consulted in the study. Derived from the literature have come out several variables that have subsequently influenced analysis and discussion of the impacts of PAPST’s CDP on the people of Gokwe. The research has made much contributions to the enlightenment of the people of Gokwe and surrounding areas of the positive and negative effects of NGOs works in Zimbabwe with PAPST being the perfect example.